Artificial Intelligence, Language, and Ethics: Re‑thinking English Language Education in India - Vasuhi, R.; Kumar S, Sabin (Journal of Neonatal Surgery, 2025)
The escalating prevalence of smartphone use among university students has precipitated documented postural alterations characterized by forward head posture, increased thoracic kyphosis, and scapular dyskinesis. This pre-post experimental study evaluated the effectiveness of an eight-week structured stretching and strengthening exercise intervention on cervicothoracic alignment, scapulothoracic kinematics, and smartphone-related postural deviations in frequent smartphone users. Sixty university students (aged 18–25 years; mean daily smartphone usage >6 hours) were enrolled in this experimental study. Participants underwent baseline measurements including three-dimensional scapulothoracic kinematic analysis, head-neck posture assessment via photogrammetry, cervical and thoracic range of motion measurement, smartphone addiction scale scoring, and ergonomic usage pattern evaluation. The intervention comprised supervised stretching exercises targeting pectoralis major and minor, upper trapezius, and sternocleidomastoid muscles, combined with strengthening protocols for deep cervical flexors, lower trapezius, serratus anterior, and rhomboid muscles, performed 5 days weekly. Outcome measurements were reassessed post-intervention. Significant improvements were observed in anterior head translation (mean reduction 12.3 mm; p<0.001), scapular dyskinesis indices (p<0.001), cervical extension range of motion (mean increase 11.5 degrees; p<0.001), and thoracic extension (mean increase 13.2 degrees; p<0.001). Smartphone Addiction Scale scores decreased by 28.4% (p<0.001), and ergonomic assessment scores improved significantly (p<0.001). These findings demonstrate that structured exercise intervention effectively ameliorates postural deviations induced by frequent smartphone use and reduces smartphone addiction behaviors in university students. The study supports integration of targeted exercise protocols in physiotherapy management strategies for smartphone-related postural disoArtificial Intelligence has rapidly entered educational spaces across the world, reshaping teaching practices and learning habits. English language education in India has been deeply influenced by this technological shift. This article examines the impact of Artificial Intelligence on English language teaching and learning in Indian schools, colleges, and universities. It focuses on students, teachers, and academic researchers. The study analyses how AI‑based tools affect language acquisition, academic writing, classroom pedagogy, and research practices. It also examines the cultural and ethical challenges created by AI use in English Studies. Drawing on theories of language acquisition, cultural studies, and educational ethics, the article integrates classroom‑based case studies from India. It argues that while AI can improve access to English language resources, it can weaken originality, cultural specificity, and academic integrity if used without regulation. The article concludes that English Studies must guide the ethical and responsible use of AI through critical literacy and policy‑based integrationrders. Results align with evidence-based musculoskeletal rehabilitation principles and current clinical practice guidelines for postural correction interventions